Clinical and radiographic comparision of primary teeth pulpotomy using formocresol, MTA and biodentine (Research, Society and Development, 2021)
Introduction: The pulpotomy procedure is conventionally done with formocresol, however, due to its mutagenic characteristics, new filling materials were developed as an alternative. Objective: The aim of this study was to review the literature in an integrative way regarding the most suitable filling material for pulpotomy in primary teeth. Methodology: The databases searched were Pubmed and Medline. The descriptors used for search were: “child”, “children”, “primary teeth”, “tooth, deciduous”, “primary tooth”, "pulpotomy", "pediatric dentistry", "endodontics", "root canal filling materials", "materials", "material", "biodentine", "mineral trioxide aggregate", "formocresol", "formocresols", "cytotoxicity", "biocompatible materials", "biocompatibility", "radiopacity", "radiographic" and "radiography, dental". The inclusion criteria were clinical studies, retrospective studies and prospective studies published from 2016 to 2021, in English or Portuguese. The exclusion criteria were thesis, dissertations, monographs, letters to the editor, textbooks and literature reviews. Results: After the search of the articles, 9 articles from both databases were included in the literature review, with higher prevalence of clinical trials. Conclusion: The most recommended filling materials for pulpotomies in primary teeth are Biodentine and Mineral Trioxide Aggregate. The filling material must be chosen according to the criteria of the professional and the patient’s case. It also needs to be considered the costs and the collaboration of the patient during the treatment.